Letter (copy) : Cheque from the Electrical Trades Union - Citrine, Walter, 1887-1983
034-0133-001 Secretary's. WMC/HVT/EC/21. 7th October, 1938. Mrs. Charlotte Haldane, The International Brigade Dependants & Wounded Aid Committee, 1, Litchfield Street, W.C.2. Dear Mrs. Haldane, Cheque from the Electrical Trades Union I am enclosing a cheque which has been forwarded to this address by the Electrical Trades Union for your Fund. The cheque has been endorsed in a manner which will enable you to pass it through your Bank. Yours sincerely, General Secretary. Cheque. 292/946/34/133